Determination of Polifenol Content and Antioxidant Activity Test of Ethanol Extract 70% Awar-Awar (Ficus septica Burm. F) Leaf using DPPH Method (1,1-Difenil-2-Pikrilhidrazil) - Any Guntarti; Devi Sahyuni Putri Koto; Mustofa Ahda; Zainab Zainab (Journal of Food and Pharmaceutical Sciences, 2019)
Free radicals are molecules with unpaired electrons that can react with body cell mollecules. As a result, cell became damaged or death because oxidation of the lipid components of cell membranes, proteins and DNA. The purpose of this study was to determine the antioxidant activity test, and total polyphenol content. The ethanol extract was done by phytochemical screening by KLT method and the antioxidant activity was performed with DPPH. The extract were obtained from 200 gram awar-awar leaf powder was macerated with 70% ethanol. Antioxidant activity was measured by DPPH purple color change. The antioxidant activity parameter was the ES50 yes obtained from the linear regression equation between the concentration and the percent of the damping. The results of phytochemical screening test of the awar-awar leaf ethanol extract showed that the sample contained flavonoid and polyphenol compounds. Determination of total phenolic content of 8,11 ± 0,364% EAG. The potential of antioxidant can be seen from the price of ES50, the value of ES50 standard quercetin of 4.542 ± 0.0767 μg / mL, ethanol extract of 21,19± 0,565 μg / mL. Data analyzed with non parametric test Krukal Wallis with 95% showed the result of ES50 of ethanol extract of awar-awar leaves was significantly different with ES50 quercetin. Conclusion of this research were ethanol extract 70% of awar-awar leaves had a total polyphenol content of 8.11% equivalents of gallic acid, and antioxidant activity of 21.19 μg / mL with very strong antioxidant strength, ie ES50 ˂50 μg / mL, while the standard quercetin was 4,542 μg / mL. Polyphenol compounds support the antioxidant activity of the extract.